Assessing ecosystem service trade-offs and synergies in the rapidly urbanizing coastal region of Mangaluru Agglomeration, India - Deeksha Nayak; Anoop Kumar Shukla (PLoS ONE, 2026)
The steady growth of the cities alters the urban environmental pattern and functions, posing signs of danger mainly on the ecosystem services. Mangaluru is a coastal city, where rapid urbanization is seen presenting both opportunities and challenges for sustaining the vital ecosystem services. In this study, we utilized InVEST (Integrated Valuation of Ecosystem Services and Trade-offs) model, a widely spread, open-source tool employed to map and quantify the benefits of ecosystem services. Water yield, carbon sequestration and soil retention are the services assessed in this study. Furthermore, we applied Ecosystem Service Trade-offs and Synergies Degree Index (ESTD) to evaluate their relationships and analyzed how various policies affected land cover and ecosystem services of Mangaluru during 1980–2022. The results showed that built up area increased at the expense of wasteland/shrubland, and agricultural land. Notable increase in water yield is observed. Carbon storage and soil loss has reduced in the study area. Between these ecosystem services, water yield presented a clear trade-off relationship with soil loss, while carbon storage was synergistic with soil loss. Our findings show that different policies have diverse consequences on the environment and ecosystem services. Under economic policies, built-up areas developed dramatically, resulting in the loss of natural land and carbon storage. Ecological policies increased water yield, and a large amount of wasteland/shrubland land was transformed into forest. The study’s conclusions will help policymakers balance economic development and environmental conservation.